Β1-adrenoceptor Arg389Gly polymorphism confers differential β-arrestin-binding tropism in cardiac myocytes. (October 2016) - McCrink, Katie A; Brill, Ava; Jafferjee, Malika; Valero, Thairy Reyes; Marrero, Christine; Rodriguez, Martha M; Hale, Genevieve M; Lymperopoulos, Anastasios
Aim: The β1 -adrenergic receptor (AR) Arg389Gly polymorphism affects efficacy of its procontractile signaling in cardiomyocytes and carriers' responses to β-blockers. To identify molecular mechanisms underlying functional differences between Arg389 and Gly389 β1 ARs, we examined their binding to β-arrestins (βarr-1 and -2), which mediate β1 AR signaling, in neonatal rat ventricular myocytes.Methods: We tested the β1 AR–βarr interaction via β1 AR immunoprecipitation followed by βarr immunoblotting.Results: βarr1 binds both variants upon isoproterenol, carvedilol or metoprolol treatment in neonatal rat ventricular myocytes. Conversely, the potentially beneficial in the heart βarr2 only interacts with the Arg389 receptor in response to isoproterenol or carvedilol.Conclusion: Arg389 confers unique βarr2-interacting tropism to the β1 AR in cardiac myocytes, potentially underlying this variant's gain-of-function phenotype and better clinical responses to β-blockers.